2019
DOI: 10.1080/10826084.2018.1524912
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pregnancy Concerns in the Relationship between Substance Use and Unprotected Sex among Adolescents

Abstract: Background: Substance use and unprotected sex are prevalent among adolescents. The link between substance use and unprotected sex is well-established. Research has also highlighted how adolescents’ attitudes and risk perceptions regarding unprotected sex, including concerns about pregnancy (“Getting pregnant would force me to grow up too fast”), are associated with unprotected sex and unplanned pregnancy. However, less research has examined the potential relationship between pregnancy concerns and substance us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Similar sentiments were also given byReardon et al, (2004) who in their national longitudinal survey of youths established that substance use was associated with unplanned pregnancy. However, a cross sectional study done among black American adolescents revealed a contrasting ndings and established that substance users (alcohol/marijuana) reported fewer pregnancy compared to non-substance users(Dir et al, 2019). The association of illicit drug use and unintended pregnancies reported in this study was in agreement with earlier reports from other geographical regions(Embersin-Kyprianou et al, 2020; McCarthy et al, 2018; Cheng et al, 2016…”
supporting
confidence: 91%
“…Similar sentiments were also given byReardon et al, (2004) who in their national longitudinal survey of youths established that substance use was associated with unplanned pregnancy. However, a cross sectional study done among black American adolescents revealed a contrasting ndings and established that substance users (alcohol/marijuana) reported fewer pregnancy compared to non-substance users(Dir et al, 2019). The association of illicit drug use and unintended pregnancies reported in this study was in agreement with earlier reports from other geographical regions(Embersin-Kyprianou et al, 2020; McCarthy et al, 2018; Cheng et al, 2016…”
supporting
confidence: 91%
“…Approximately 16% of adolescents have ridden in a vehicle with someone who had been drinking, and 13% of U.S. high schoolers reported they had driven while under the influence of cannabis over the past month (15). Adolescents who use substances are also more likely to engage in unprotected sex (16), and among the 28.8% of adolescents who report being currently sexually active, more than half were under the influence of alcohol or other substances before they last engaged in sexual intercourse (15).…”
Section: Substance Usementioning
confidence: 99%